The application of drug loading and drug release characteristics of two-dimensional nanocarriers for targeted treatment of leukemia - Yao, Yuan; Gao, Xiaoli; Zhou, Zaifu (Frontiers in Materials, 2023)
The development of bioinformatics technology has greatly contributed to the role of nanomedicine in drug delivery systems. The advantages of low toxicity, minimal side effects, high efficiency, and controllable drug release make it highly effective in targeted treatment. Based on the two-dimensional nanomedicine characteristics of black phosphorus, experimental designs were conducted to prepare the nanosheet, modify with Polyethylene glycol (PEG), and load anti-tumor drugs. Experimental analysis was carried out to characterize nanomedicine, drug release, and targeted treatment. The results showed that PEG modification effectively improved the negative charge of black phosphorus (BP) nanocrystals, demonstrating good thermal stability. The release of doxorubicin hydrochloride (DOX) loaded nanoparticles was analyzed. It was found that the maximum drug release efficiency of BP-PEG-DOX was higher than that of BP-DOX at pH 5 and 7.5 (12.13%>7.69%, 29.46%>28.69%).The maximum release rate of BP-PEG-DOX-NIR reached 33.23% and 28.67% at 35℃ and 45℃, respectively, with a difference of more than 10% compared to the group without laser. The nanodrug particles modified with PEG and laser treatment showed a significant killing effect on cells, with a decrease in cell survival rate exceeding 15%, demonstrating high safety and effectiveness in targeted treatment of acute T lymphoblastic leukemia cells. BP nanomedicine has profound application value in novel targeted tumor therapy, improving drug effectiveness and specificity.